Pengaruh partisipasi penganggaran, Job Relevant Information (JRI) dan volatilitas lingkungan terhadap kinerja manajerial pada perusahaan manufaktur di Indonesia - A Setya Marsudi; Imam Setya Ghozali (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2001)
The study attempts to examine the relationship between budgetary participation and individual performance. In so doing the study include the level of Job Relevant Information (JRI) is treated as an intervening variable, and at the same time considers environmental volatility as a moderating variables.Data for this study were collected by using questionnaires, which were mailed to 500 department managers chosen from Indonesian Capital Market Directory. There were 74 responses of which 68 were complete and hence usable.The study concludes that the budgetary participation effects the individual performance through JRI. Environmental volatility has no significant effects on budgetary participation and did not moderate the effects of participative budgeting on JRI. Interactions between environmental volatility and JRI had no significant effect on managerial performance.